"It's embarrassing to come here": Welfare‐to‐work, emotion rules, and emotional capital. Issue 1 (27th February 2022) - Turgeon, Brianna; Root, Kaitlyn; Ray, Kasey; Taylor, Tiffany
Abstract: Neoliberal discourse about achievement impacts our cultural expectations for how people on welfare "should" feel regarding work, motivation, and shame. In this paper, we build on the literature on emotions, work, and inequality by examining the embeddedness of feeling rules in welfare‐to‐work programs. We analyze interviews with Ohio Works First cash assistance program managers in Ohio counties ( n = 69) to understand how managers emphasize emotional displays that make clients more desirable to employers. We argue that welfare‐to‐work county managers value emotional capital based in the neoliberal and paternal ideologies of the State. We find that welfare managers use emotion rules to (1) emphasize pride and the role of emotional capital in workplace success and (2) invoke shame to discourage workplace failure. By emphasizing emotional capital as a pathway to success, Ohio Works First managers underplay structural factors contributing to poverty and social mobility. 摘要: 关于成就的新自由主义话语影响着我们对"接受福利救济金的人们在工作、动机和羞耻方面'应该'如何感受"的文化期望。本文中，我们分析了"从福利转向工作"项目中情感规则的嵌入性，进而对有关情绪、工作和不平等的文献作贡献。我们对俄亥俄州69个县的"俄亥俄州工作第一"现金援助项目经理进行访谈，并分析访谈数据以期理解项目经理如何强调情绪表达，后者帮助客户提升其雇佣价值。我们论证认为，负责"从福利转向工作"项目的县级经理所重视的情绪资本基于该州新自由主义式和父系式意识形态。我们发现，项目经理使用情绪规则来1）强调自豪和情绪资本在引领工作成功一事中发挥的作用，2）引起羞愧，以期不鼓励工作失败。通过将情绪资本作为成功之路加以强调，"俄亥俄州工作第一"项目经理淡化了导致贫困和社会流动的结构性因素。 Resumen: El discurso neoliberal sobre el logro afecta nuestras expectativas culturales sobre cómo las personas que reciben asistencia social "deberían" sentirse con respecto al trabajo, la motivación y la vergüenza. En este artículo, nos basamos en la literatura sobre las emociones, el trabajo y la desigualdad al examinar la integración de las reglas de los sentimientos en los programas de asistencia social al trabajo. Analizamos las entrevistas con los gerentes del programa de asistencia en efectivo de Ohio Works First en los condados de Ohio (n=69) para comprender cómo los gerentes enfatizan las demostraciones emocionales que hacen que los clientes sean más deseables para los empleadores. Argumentamos que los administradores del condado de Welfare‐to‐Work valoran el capital emocional basado en las ideologías neoliberales y paternalistas del Estado. Encontramos que los gerentes de bienestar usan reglas de emoción para 1) enfatizar el orgullo y el papel del capital emocional en el éxito en el lugar de trabajo y 2) invocar la vergüenza para desalentar el fracaso en el lugar de trabajo. Al enfatizar el capital emocional como un camino hacia el éxito, los gerentes de Ohio Works First minimizan los factores estructurales que contribuyen a la pobreza y la movilidad social.